PUPILLARY REFLEX AT EASE: A new instrument for the demonstration of Pupillary reflex - Allapitchai Fathima; Praveena Shyam; Shivam Gupta; Meenakshi Ravindran (Indian Journal of Ophthalmology)
As ophthalmologists, we often come across a lot of patients with neuro-ophthalmological disorders that show no positive examination findings except for subtle abnormalities in the pupillary light reflex. However, these subtle changes are often overlooked in a busy OPD setting, especially by junior doctors and nursing staff. Thus, we decided to develop an innovation to simplify the assessment of pupillary reflexes, which we have named PUPILLARY REFLEX AT EASE. Our plan involved magnifying the iris and pupil using biconvex lenses to facilitate the visualization of the response. Additionally, we proposed setting up an inbuilt electrical circuit for illuminating the eyes. To elicit consensual reflexes, we decided to dissociate the eyes and provide ambient illumination using low-voltage light bulbs. This represents a simple attempt to address a common challenge faced by clinicians.